Types of Pattern Strabismus and Their Surgical Outcomes after Adjustable Strabismus Surgery: Doi:10.36351/pjo.v37i1.1049 - Nadeem, Sana (Pakistan Journal of Ophthalmology, 2020)
Purpose: To study the different types of pattern strabismus and their surgical outcomes after adjustable strabismus surgery. Study Design: Prospective, interventional study. Place and Duration of Study: Eye department, Fauji Foundation Hospital, Rawalpindi (June, 2016 to March, 2019). Methods: A total of 40 consecutive patients with pattern strabismus were included in the study. After complete orthoptic assessment, the patients underwent either rectus muscle transposition or oblique muscle surgery, by adjustable squint surgery. The pre-operative evaluation of different strabismus patterns, deviations, and post-operative results were measured and analyzed. The amount of postoperative pattern change was measured at 6 weeks postoperatively, to assess the success of the surgeries. Results: Out of 40 patients, 33 were females and 7 were males. The age ranged from 7 to 69 years (mean 18.05 ± 9.6). All patients were operated by using adjustable suture technique. “V” pattern was seen in 26 cases (65%) and “A” pattern was seen in 12 (30%) cases. The mean preoperative pattern was 13.2 ± 8.09 PD (prism diopters), and the mean postoperative pattern was 2.05 ± 2.96 PD. Surgical success was defined as the amount of pattern collapse at 6 weeks, the period at which a stable alignment was achieved. The difference between the preoperative and postoperative pattern deviation was statistically significant (p = 0.000). Correction of the pattern was seen in 92.5% of patients at average follow up of 50.87 ± 14.02 days. Conclusions: Pattern Strabismus can be corrected by varying rectus muscle transpositions or oblique muscle surgery during routine adjustable strabismus surgery. Key Words: Strabismus, V pattern, A pattern, Y pattern, X pattern, lambda pattern, muscle transposition.